Case Report: Long Progression-Free Survival of Immunotherapy for Lung Adenocarcinoma With Epidermal Growth Factor Receptor Mutation - Peng, Jianfeng; Zhao, Xianguang; Zhao, Kaikai; Meng, Xiangjiao (Frontiers in Oncology, 2021)
[Background] Immune checkpoint inhibitors (ICIs) has been clinically proven to be efficient in non-small cell lung cancer (NSCLC). However, it has also been found that immunotherapy is not effective for all patients. For instance, some patients with epidermal growth factor receptor (EGFR) mutation tumors have a low overall response rate to ICIs. As a result, we retrospectively analyzed the efficacy of anti-PD-L1 blockade (atezolizumab) treatment for a patient with EGFR mutation and explored the interaction between immunotherapy and EGFR mutations in NSCLC. [Case Presentation] A patient, 62-year-old non-smoking female, with lung adenocarcinoma was initially misdiagnosed as EGFR wild-type, received a third-line treatment with atezolizumab experiencing partial response (PR) and progression-free survival (PFS) for 23 months. She had later been confirmed with EGFR L858R mutation prior to taking atezolizumab. On top of that, the patient developed T790M mutation after administered atezolizumab instead of EGFR-TKIs. She started with osimertinib, the lesion continued to progress though. Tumor mutation burden, PD-L1 expression and tumor infiltrating lymphocytes had been tested for further analysis. [Conclusion] The case report and literature review indicate that ICIs might be more effective to L858R mutation than to other EGFR mutant subtypes, which correlates with certain potential predictors such as tumor mutation burden (TMB) and concurrent programmed death-ligand 1 (PD-L1) plus CD8+ tumor infiltrating lymphocyte (TIL) expression. However, there is no report on progression from non-primary EGFR T790M mutation to T790M mutation who neither previously suffered from EGFR-TKIs nor responded to osimertinib. This case report will offer some information to guide the investigation how to identify who can be benefited from immunotherapy and who does not respond to EGFR-TKIs among the patients with EGFR mutations.